2018
DOI: 10.5194/acp-18-4803-2018
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of the mesospheric quasi-stationary planetary waves in the unusual Arctic winter 2015/2016

Abstract: Abstract. The midwinter 2015/2016 was characterized by an unusually strong polar night jet (PNJ) and extraordinarily large stationary planetary wave (SPW) amplitudes in the subtropical mesosphere. The aim of this study is, therefore, to find the origin of these mesospheric SPWs in the midwinter 2015/2016 study period. The study duration is split into two periods: the first period runs from late December 2015 until early January 2016 (Period I), and the second period from early January until mid-January 2016 (P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 34 publications
1
44
2
Order By: Relevance
“…In some cases, also local instabilities indicated by the reversals in the q y generate new SPWs 1 in the polar region (Charney and Stern, 1962;Garcia, 1991), which cause an additional transfer of momentum and energy. These local instabilities are also observed in the lower mesosphere, so that the SPWs 1 also have a lasting effect on the MLT region see (Smith, 2003;Lieberman et al, 2013;Matthias and Ern, 2018). For those GW hotspots, which are in phase with the modeled SPW 1 and do not create a negative n in the upper polar region, the SPWs 1 propagate through the polar region further upward and influence the polar vortex up to an altitude of 70 km.…”
Section: Discussionmentioning
confidence: 95%
“…In some cases, also local instabilities indicated by the reversals in the q y generate new SPWs 1 in the polar region (Charney and Stern, 1962;Garcia, 1991), which cause an additional transfer of momentum and energy. These local instabilities are also observed in the lower mesosphere, so that the SPWs 1 also have a lasting effect on the MLT region see (Smith, 2003;Lieberman et al, 2013;Matthias and Ern, 2018). For those GW hotspots, which are in phase with the modeled SPW 1 and do not create a negative n in the upper polar region, the SPWs 1 propagate through the polar region further upward and influence the polar vortex up to an altitude of 70 km.…”
Section: Discussionmentioning
confidence: 95%
“…These SPWs 1 are breaking around 50 km between 50 and 80 • N and lead to an enhanced negative EP divergence connected with a decreasing zonal mean zonal wind at higher latitudes. In the lower mesosphere between 40 and 70 • N there is a second source of SPW 1 (positive EP divergence) developed as well due to local baroclinic instabilities (reversal of the q y ) (Smith, 2003;Lieberman et al, 2013;Matthias and Ern, 2018). As a consequence, the EP flux and the SPW 1 amplitude are enhanced between 70 and 80 km, right above the positive EP divergence anomaly.…”
Section: Propagation Conditions For Spwsmentioning
confidence: 97%
“…In a model climatology Chandran et al (2013) found that 68 % of the SSWs with elevated stratopause are split-type events and that the remaining 32 % are displacement events. Matthias et al (2012) compiled a composite of SSW events with an elevated stratopause between 1998 and 2011 using ECMWF data and MF-radar observations revealing the for- mation of an elevated stratopause in the mesospheric wind as strong zonal wind enhancement after the SSW. Later, Limpasuvan et al (2016) made a composite analysis of SSWs with an elevated stratopause using WACCM data and explained the occurrence of an elevated stratopause with strong, waveinduced downwelling in the mesosphere which leads to adiabatic warming.…”
Section: Observations At Ny-ålesundmentioning
confidence: 99%